Penerapan Pre-Sale Disclosure sebagai Perlindungan Hukum Pembeli Bentuk Bisnis “Business Opportunity Ventures” Ditinjau melalui Undang-undang Republik Indonesia Nomor 8 Tahun 1999 tentang Perlindungan Konsumen - Astrid Amidiaputri Hasyyati; Mukhammad Tismandico Ilham Zulfikar; Kadek Deddy Permana Artha; Arif Rahman (JURNAL MERCATORIA, 2020)
The form of business "Business Opportunity Ventures" that has developed in Indonesia has the same meaning as the franchise business form, but the two business forms are basically different. BO is regulated in the Business Opportunity Sales Law of 1995 by the Federal Trade Commission of the United States. Different forms of business certainly require different arrangements. This is motivated by the reason that the business forms that have not been regulated in a law are prone to fraud and injustice in the transaction process. buyers of this form of business. In this study using a normative juridical method with the statutory approach, conceptual approach, and comparative approach. Fraud and injustice received by BO Buyers can be done legally through the Consumer Dispute Settlement Agency as stipulated in the UUPK.